(3YedjGJ ZSd GdCehGd hBdjGJ ecGaMJgGs - (3eMeO Ydj(B, (3GdYQjGfs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 2005)
(3eaghe XGgQI ZSd GdCehGd (B: (3GdBdjGJ GdOhdjI hZSd GdCehGd, OhQ GdGJaGbjGJ GdOhdjI aj ecGaMI YedjGJ ZSd GdCehGd, JMQje YedjGJ ZSd GdCehGd habG ddGJaGbjGJ GdOhdjI, GdCdjGJ GdhWfjI hZSd GdCehGd, ecGaMI YedjGJ ZSd GdCehGd aj GdJTQjY GdaQfSj, ecGaMI YedjGJ ZSd GdCehGd aj GdCfXeI GdbGfhfjI GdCNQi, ecGaMI YedjGJ ZSd GdCehGd aj GdJTQjY GdeUQj Qbe (B80 (3dSfI (B2002(3, GdJWhQ GdJTQjYj decGaMI YedjGJ ZSd GdCehGd, GdHfjGf GdbGfhfj dLQjeI ZSd GdCehGd, GdLQGFe GdedMbI dLQjeI ZSd GdCehGd, hSGFd ecGaMI LQjeI ZSd GdCehGd(B.s
(3GdeQGLY U(B. 612s
Keywords: (3GdLQGFe GdJLGQjIs; (3LQGFe GdCehGds; (3ZSd GdCehGd(B- (3bhGfjf hJTQjYGJs